Climate Change affects everyone - Developed and Developing countries - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Ephraim Kamuntu, Minister for Water and the Environment of Uganda says that Climate Change affects every country. Video by Meerim Shakirova, soical media reporter